UNDERSTANDING THE SIGNIFICANCE OF MERCHANDISING ANALYSIS IN MEDICINE - Juraeva Barno G’ulom qizi; Shopulatov Mirjalol Kamoliddin og’li; Burkhanova Shakhlokhon Davronkhonovna (Western European Studies, 2024)
This research paper explores the significance of merchandising analysis in the field of medicine, focusing on its role in optimizing patient care, operational efficiency, and financial sustainability within healthcare institutions. Through an examination of procurement, distribution, and utilization practices of medical supplies, devices, and pharmaceuticals, this paper demonstrates how merchandising analysis contributes to inventory management, costeffectiveness, and quality of care delivery. By analyzing purchasing patterns, inventory turnover rates, and supplier performance, healthcare organizations can identify opportunities for cost savings, negotiate favorable contracts, and mitigate supply chain risks. Furthermore, the paper discusses how merchandising analysis supports evidence-based decision-making, clinical practice, and strategic initiatives such as value-based purchasing and population health management. The findings emphasize the importance of leveraging data-driven insights and best practices in supply chain management to achieve operational excellence and deliver valuebased care in the evolving healthcare landscape
Keywords: merchandising; cost-effectiveness; clinical practice; business principles